The Inuence of Cross-Section Shape of the Car Roof Rail on the Quqsi-Dynamic Buckling Modes - Mróz, Andrzej (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2013)
This paper presents the results of numerical analysis of the aluminium profiles subjected to dynamic, of different time duration impulse loading. The analysis includes the change in cross–section of the roof rail, ranging from the open ”C profile”, through closed ”Rectangular” to hybrid ”Tandem with brackets”. The main aim of this study is to model the dynamic response of the car roof rail to impulse loading, which may appear in case of collision.
Keywords: aluminium; thin–walled profiles; automotive application; quasi–dynamic analysis; aluminium; profile cienkościenne; analiza quasi dynamiczna; aplikacja samochodowa